2016
DOI: 10.1155/2016/9289684
|View full text |Cite
|
Sign up to set email alerts
|

Steady Flow of Couple-Stress Fluid in Constricted Tapered Artery: Effects of Transverse Magnetic Field, Moving Catheter, and Slip Velocity

Abstract: Steady flow of a couple-stress fluid in constricted tapered artery has been studied under the effects of transverse magnetic field, moving catheter, and slip velocity. With the help of Bessel’s functions, analytic expressions for axial velocity, flow rate, impedance, and wall shear stress have been obtained. It is of interest to note that these solutions can be used for different types of fluid flow in tubes and not only the case of blood. The effects of various geometric parameters, the parameters arising out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Vardanyan [23] demonstrated that the use of a magnetic field diminishes the velocity of blood motion. Therefore, all researchers reported that the use of magnetic influence decayed the blood flow [24]. The researchers used various methods to measure the blood flow and some of the techniques depend on the thermal properties to predict the temperature of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Vardanyan [23] demonstrated that the use of a magnetic field diminishes the velocity of blood motion. Therefore, all researchers reported that the use of magnetic influence decayed the blood flow [24]. The researchers used various methods to measure the blood flow and some of the techniques depend on the thermal properties to predict the temperature of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the tapered stenosed artery is shown in figs. 2(a) and 2(b), and can be expressed mathematically as [32]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…1A, pp. [29][30][31][32][33][34][35][36][37][38][39][40] are made in this subject, as presented in [8][9][10]. This type of calculus allows defining precisely non-integer order derivatives or integrals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakhti and Azrar [9] studied the steady flow of a couplestress fluid through constricted tapered artery under influence of a transverse magnetic field, moving catheter, and slip velocity. Solutions to velocity and shear stress are expressed with Bessel's functions.…”
Section: Advances In Mathematical Physicsmentioning
confidence: 99%